Markers for Significant or High-Grade Prostate Cancer in Patients over 75 Years Undergoing Prostatic Biopsy - Vahudin Zugor; Melanie von Brandenstein; Ali Tok; Apostolos P. Labanaris; Ilgar Akbarov (International Journal of Prostate Cancer, 2017)
Purpose: To show the increased necessity of routine prostate biopsy in men older than 75 years and to identify markers, which reliably indicate the presence of a prostate cancer (PCa), we evaluate several different parameters from elderly patients. Methods: 196 patients over 75 years were included in the study, inclusion criteria for the biopsy were: PSA levels >4 ng/ml and/or a suspicious finding on dig ital rectal examination (DRE). The parameters analyzed included: age, prostate size, PSA levels, DRE findings, American Society of Anesthesiologists (ASA) PCa detection rate, Gleason score, clinically significant PCa detection rate and type of therapy once PCa had been detected (curative intent or palliative intent). Results: PCa was detected in N=115 patients (59%), with 84.3% of them being defined as clinically significant (p<0.05) and 60.8% (p<0.05) as high grade. Only a PSA level > 10 ng/ml with a simultaneous positive DRE finding was a marker for high-grade or significant PCa (p< 0.001) in patients >70 years. Conclusions: Our findings demonstrate that the prevalence of significant and high-grade PCa in the elderly patients is high raised ( 60%). We identified two significant markers for patients over the age of 75, namely an increased high PSA level (PSA>10 ng/ml) and positive DRE. The combination of both markers indicates that the patient is suffering under a significant and high-grade PCa. In our opinion, every patient showing a combinational increase of both markers should be biopsied in order to receive an adequate therapy.
Keywords: prostate cancer